2015
DOI: 10.1007/s10549-015-3467-3
|View full text |Cite
|
Sign up to set email alerts
|

ERβ1 inversely correlates with PTEN/PI3K/AKT pathway and predicts a favorable prognosis in triple-negative breast cancer

Abstract: In contrast to the well-established role of estrogen receptor alpha (ERα) in breast cancer, the significance of estrogen receptor beta (ERβ) remains controversial, especially in triple-negative breast cancer (TNBC). We sought to investigate the clinical importance of wild-type ERβ (ERβ1) in TNBC based on a large population, and to explore the potential molecular pathways involved in. A total of 571 patients with invasive TNBC undergoing curative surgery were included in this study. Immunohistochemical staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 53 publications
3
73
0
Order By: Relevance
“…Our results regarding chemotherapy were in accordance with the recent study by Wang and colleagues, in which high ERb1 tumor expression was an independent prognostic marker for chemotherapy-treated patients with TNBC tumors without endocrine treatment or trastuzumab (16). The finding was also supported by a neoadjuvant study, in which high pretreatment ERb expression was associated with lower proliferation rates and better pathologic response in the posttreatment samples (38).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results regarding chemotherapy were in accordance with the recent study by Wang and colleagues, in which high ERb1 tumor expression was an independent prognostic marker for chemotherapy-treated patients with TNBC tumors without endocrine treatment or trastuzumab (16). The finding was also supported by a neoadjuvant study, in which high pretreatment ERb expression was associated with lower proliferation rates and better pathologic response in the posttreatment samples (38).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we tried to address the above-mentioned issues by choosing a cutoff for which we could observe both associations with established clinicopathological characteristics and prognostic impact, as has been done previously (14,16,48). The recent meta-analysis reported ERb1 þ of 67% across studies, in spite of varying cut-off point definitions (11), and we reported ERb1 75 þ of 73%.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In agreement with our data, ERβ ligands have been previously shown to exert their antitumor effects through inactivation of RAS as well as of the PI3K/Akt pathway in some cancer cells (94, 141, 142). Moreover, Wang and coworkers (143) have recently reported an inverse correlation between the expression of ERβ and the activity of the PI3K/Akt pathway in aggressive, triple-negative, breast cancer. Chen et al (141) demonstrated that, in breast cancer cells, the isoflavone calycosin activates ERβ, and this is followed by a decreased activity of the PI3K/Akt pathway; on the other hand, calycosin did not affect the activity of the MAPK/ERK cascade.…”
Section: Antitumor Activity Of Erβ In Melanomamentioning
confidence: 99%